Pengendalian Kualitas Produk Teh di PT XYZ Menggunakan Pendekatan Six Sigma - Ardhaneswari, Pande Putu Narisya; Priambadi, I Gusti Ngurah; Setiawati, Ni Luh Putu Lilis Sinta (Metode : Jurnal Teknik Industri, 2024)
PT XYZ is a company specializing in the bottled tea beverage industry. The company is experiencing quality control challenges, evidenced by a defect rate of 0.9%, which exceeds the target of 0.2%. This study aims to identify the reasons for the high defect rate in tea production and provide recommendations for improvement. Utilizing the Six Sigma approach along with the DMAIC (Define, Measure, Analyze, Improve, and Control) methodology can help maintain product quality by identifying the sources of defects in tea products at PT XYZ. The research identified three main types of defects: insufficient volume, lack of crown, and non-standard temperature. The most prevalent defect was non-standard temperature, accounting for 7,968 defective items (60%). The causes of these defects include human factors such as operator negligence and lack of precision, material factors such as low tea temperature and decreased bottle temperature, method factors like improper and inaccurate inspection methods in the Quality Control Division, machine factors such as low caustic temperature in the washer machine, and environmental factors like high room temperature. Recommended improvements include conducting regular training sessions for operators to enhance their understanding of their work areas, especially in monitoring the production process. Additionally, thorough quality checks should be performed in line with the steps outlined in the work instructions. To reduce defects and errors in packaging machines, regular maintenance is essential to ensure their smooth operation.